2020
DOI: 10.1038/s41431-020-00770-0
|View full text |Cite|
|
Sign up to set email alerts
|

Long-read trio sequencing of individuals with unsolved intellectual disability

Abstract: Long-read sequencing (LRS) has the potential to comprehensively identify all medically relevant genome variation, including variation commonly missed by short-read sequencing (SRS) approaches. To determine this potential, we performed LRS around 15×–40× genome coverage using the Pacific Biosciences Sequel I System for five trios. The respective probands were diagnosed with intellectual disability (ID) whose etiology remained unresolved after SRS exomes and genomes. Systematic assessment of LRS coverage showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
0
27
1
Order By: Relevance
“…Long-read sequencing technologies have been rapidly developing and seem to overcome the limitations of short reads in genetic research and molecular diagnoses of different human genetic diseases. 21 , 22 , 23 , 24 Their read length of several kilobases (1) simplifies the identification of SVs, 25 , 26 , 27 , 28 (2) simplifies the spanning of repeats and high GC-rich regions, 29 , 30 and (3) enables variant phasing. 24 , 31 , 32 Bionano optical genome mapping is a high-resolution cytogenetic technique and is based on ultra-high molecular weight (UHMW) DNA molecules that are fluorescently labeled at a 6-mer motif (CTTAAG).…”
Section: Introductionmentioning
confidence: 99%
“…Long-read sequencing technologies have been rapidly developing and seem to overcome the limitations of short reads in genetic research and molecular diagnoses of different human genetic diseases. 21 , 22 , 23 , 24 Their read length of several kilobases (1) simplifies the identification of SVs, 25 , 26 , 27 , 28 (2) simplifies the spanning of repeats and high GC-rich regions, 29 , 30 and (3) enables variant phasing. 24 , 31 , 32 Bionano optical genome mapping is a high-resolution cytogenetic technique and is based on ultra-high molecular weight (UHMW) DNA molecules that are fluorescently labeled at a 6-mer motif (CTTAAG).…”
Section: Introductionmentioning
confidence: 99%
“…This experimental RNAseq approach currently remains widespread (3,10,(13)(14)(15); however, our model may be readily applicable to RNA-seq generated using alternative methodologies, such as increased read length, with only minor variations in model performance ( Supplementary Figure 3). As other technologies, such as long-read (36)(37)(38), singlecell (39,40) and spatially resolved RNA-seq (41)(42)(43)(44), become more prevalent in a clinical setting, appropriate control datasets must be generated to develop corresponding MRSD models. Similarly, recent research has shown noticeable improvements to diagnostic yield for neuromuscular disorders by conducting RNAseq on in vitro myofibrils generated by a fibroblast-to-myofibril transdifferentiation protocol (45).…”
Section: Discussionmentioning
confidence: 99%
“…Despite complete genome coverage in WGS, short-read technologies (Solexa/Illumina) may miss more complex structural rearrangements and even CNVs. Future perspective: Long-read WGS (based on PacBio sequencing, for example) is a promising approach to overcome these limitations [16,17].…”
Section: Copy Number Variationsmentioning
confidence: 99%
“…Long-read NGS (e.g., PacBio) can conquer this problem. With contiguous reads of up to 60 kb [16], even distant variants can be attributed to the same or separate alleles (▶ Fig. 3).…”
Section: Diagnostic Pitfallsmentioning
confidence: 99%